UFIDA (C) - Chen, E.; McFarlan, F. Warren (Franklin Warren); Xia, Donglin ([London] : SAGE, 2016)
In June 2010, after a decade of financial success, Wang Wenjing, Chairman and President of UFIDA, reflected on the ten-year evolution of the UFIDA control system, which had developed from a basic budgeting scheme into a comprehensive management system. Though UFIDA effectively expanded upon the initial business model to establish the current corporate organization, Wang expressed concerns about the additional strategic changes needed to transform UFIDA into an internationally acclaimed software company. When UFIDA completed its IPO in 2001, it was apparent to Wang that its current operation management system was not suitable for a listed company. This case study discusses this topic.
Originally Published in: Chen, E., McFarlan, F.W., Xia, D. (2011). UFIDA (C). 0-310-113. Beijing: Tsinghua SEM China Business Case Center.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; UFIDA (Firm); Business enterprises -- Finance -- Case studies; Personnel management -- Case studies; Computer software industry -- Management -- Case studies